The impact of hypoglycaemia on quality of life outcomes among adults with type 1 diabetes: A systematic review. (April 2021) - Chatwin, Hannah; Broadley, Melanie; Speight, Jane; Cantrell, Anna; Sutton, Anthea; Heller, Simon; de Galan, Bastiaan; Hendrieckx, Christel; Pouwer, Frans; ,
Abstract: Hypoglycaemia is a common barrier to optimal glycaemic management and often feared among adults with type 1 diabetes. The aim of this systematic review was to summarize current evidence regarding the impact of hypoglycaemia on quality of life (QoL) and related outcomes. Electronic searches of MEDLINE, PsycINFO, CINAHL, Cochrane Database of Systematic Reviews, and Cochrane Central Register of Controlled Trials were conducted. Peer-reviewed empirical studies investigating the relationship between hypoglycaemia and QoL were eligible for inclusion. Thirty studies met the inclusion criteria. Extracted data was summarized in a narrative synthesis according to Synthesis Without Meta-Analysis guidelines. None of the studies examined the impact of hypoglycaemia on general QoL. There was no association between hypoglycaemia and diabetes-specific QoL in four of the 30 studies. Severe hypoglycaemia was associated with greater fear of hypoglycaemia and diabetes distress, and lower general emotional well-being, but not with depression, anxiety, or health status. Self-treated hypoglycaemia was associated with greater fear of hypoglycaemia. With the exception of fear of hypoglycaemia, this review shows mixed associations between hypoglycaemia and psychological outcomes. Further research is needed to investigate the impact of hypoglycaemia on other domains of QoL.